Enhanced Transdermal Delivery of Cilnidpine Via Ultradeformable Vesicle Loaded Patch: Statistical Optimization, Characterization and Pharmacokinetic Assessment - Reddy, Dagada Maheswara; Mohan, Mothilal (Pharmaceutical Nanotechnology, 2025)
ObjectiveThe study aimed to address the limitations of oral delivery and enhance the bioavailability of Cilnidipine (often prescribed as antihypertensive drug) (CND) through the development of transdermal patches containing ultra-deformable transferosomes.MethodsCND, known for its low oral bioavailability and adverse effects, was encapsulated in transferosomes using a thin film hydration method. Seventeen formulations were made (using Box Behnken Design), varying Soya lecithin, Tween-80, and rotary evaporator’s speed, and evaluated for vesicle size, polydispersity index (PDI), and entrapment efficiency (EE %). The better formulation was selected based on these parameters and incorporated into transdermal patches. Physicochemical properties, in-vitro and ex-vivo permeation, and skin irritancy studies were conducted on the patches. Pharmacokinetic studies were conducted using male Wistar albino rats.ResultsThe study found that the developed transferosomal formulations had vesicle sizes between 185 nm and 401 nm, entrapment efficiency (EE%) between 63% and 92%, and zeta potential ranging from -52 mV to -20 mV. Both in-vitro and ex-vivo permeation studies showed that transferosomal formulations provided significantly better drug permeation than plain Cilnidipine patches, with increased permeation linked to higher PEG-400 concentrations. The transferosomal patches did not cause skin irritation. The optimized formulation exhibited a higher % drug release (85.7±1.5%). In pharmacokinetic studies using male Wistar albino rats, the transferosomal patch CTP-17 demonstrated a higher maximum concentration (Cmax) of 1565.068 mcg/ml and a greater area under the curve (AUC) of 13225.352 μg h/ml compared to oral administration.ConclusionThe study concludes that the transferosomal patches of CND offer a promising approach for effective transdermal delivery, potentially improving hypertension management for prolonged periods in a controlled manner.
Keywords: hypertension management